2011
DOI: 10.1259/bjr/40806022
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of mammographic breast composition measurements: towards a quantitative measure of relative breast cancer risk

Abstract: Objective: A number of studies have identified the relationship between the visual appearance of high breast density at mammography and an increased risk of breast cancer. With the advent of digital mammography and the promise of routine measurements of parameters associated with breast composition, the possibility arises of using breast composition in a quantitative manner to predict relative breast cancer risk. Previous measurements have shown that the average proportion of glandular and adipose tissue withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…2016 ). The glandular tissue proportion varies according to the breast size and patient age ( Kotre 2011 ). Moreover, some works have shown that the ethnicity of the women and their geographical location are also factors relevant to breast density, which are associated with socio-economic conditions and lifestyle ( Aitken et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016 ). The glandular tissue proportion varies according to the breast size and patient age ( Kotre 2011 ). Moreover, some works have shown that the ethnicity of the women and their geographical location are also factors relevant to breast density, which are associated with socio-economic conditions and lifestyle ( Aitken et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that alternative imaging tests should be used for dense breasts, such as ultrasound or digital breast tomosynthesis (DBT), since these are not as affected by the amount of glandular tissue (Boyd et al 2007; Ko et al 2014;Vilaverde et al 2016). The glandular tissue proportion varies according to the breast size and patient age (Kotre 2011). Moreover, some works have shown that the ethnicity of the women and their geographical location are also factors relevant to breast density, which are associated with socio-economic conditions and lifestyle (Aitken et al 2010;Moore et al 2020;Perry et al 2008;Van der Waal et al 2015;Viel and Rymzhanova 2012;Zulfiqar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 below. Kotre CJ [5] consents that "It is demonstrated that a nonlinear transformation can be used to produce normal statistical distributions, suitable for producing a standardized "Z-score" for breast composition. A standard "Z-score" approach to identify women with unusually glandular breasts is recommended and so provide a basis for cancer risk estimations".…”
Section: Introductionmentioning
confidence: 99%